Acquired qnrVC1 and blaNDM-1 resistance markers in an international high-risk Pseudomonas aeruginosa ST773 clone. Issue 3 (22nd January 2019) - Kocsis, Bela; Toth, Akos; Gulyas, Daniel; Ligeti, Balazs; Katona, Katalin; Rokusz, Laszlo; Szabo, Dora
Abstract : A multidrug-resistant Pseudomonas aeruginosa PS1 isolated from urine clinical sample was investigated in this study. The strain exhibited resistance to piperacillin/tazobactam, ciprofloxacin, imipenem, ceftazidime but it was susceptible to colistin. Analysis of whole-genome sequencing data by ResFinder detected various resistance determinants including qnrVC1 and bla NDM-1. The multiresistant P. aeruginosa isolate belonged to ST773 high-risk clone. The qnrVC1 and bla NDM-1 determinants were incorporated into different integrons. Expression of bla NDM-1 was fourfold and qnrVC1 was twofold increased, compared to that of rpsL housekeeping gene. Mutations in gyrA Thr83Leu and parC Ser87Leu were detected and additionally qnrVC1 expression indicates protective effect of QnrVC1 pentapeptid protein on gyrase and topoisomerase. High-risk P. aeruginosa clones integrate various carbapenemase and other resistance determinants into their genomes that facilitates further dissemination of multiresistance among clinical isolates. We report bla NDM-1 and qnrVC1 genes in P. aeruginosa ST773 international high-risk clone.